A binder for electrochemical energy storage device, preparation method and application thereof

A polyacrylate-based binder with a cross-linking agent forms a rigid network structure to address the flexibility and stability issues of existing binders, improving the mechanical properties and cycle life of lithium-ion batteries and supercapacitors.

CN118197818BActive Publication Date: 2025-01-03ANHUI PUMIYANG NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410297433.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2025-01-03
Estimated Expiration
2044-03-15

AI Technical Summary

Technical Problem

Current binders for lithium-ion batteries and supercapacitors, such as PTFE and PVDF, have poor flexibility, are expensive, and cannot maintain long-term mechanical stability due to molecular weight decrease and viscosity changes, leading to electrode material detachment and capacity decay.

Method used

A binder composed of polyacrylate with epoxy groups and a cross-linking agent is used to form a network structure with good rigidity and adhesion, applied in the electrode sheet preparation process, which includes a cross-linking reaction at a certain temperature.

Benefits of technology

The binder improves the bonding effect and stability of the electrode, enhancing the capacity and cycle life of electrochemical energy storage devices by forming a three-dimensional network structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure GHA0000007941980000021
    Figure GHA0000007941980000021
  • Figure GHA0000007941980000022
    Figure GHA0000007941980000022
Patent Text Reader

Abstract

The present invention proposes an application of a binder for an electrochemical energy storage device, wherein the binder is applied to the preparation process of an electrode sheet, wherein the electrode sheet is composed of a powdered active substance, a powdered conductive agent, and a binder, and comprises, by mass fraction, 70-98% of the powdered active substance, 1-10% of the powdered conductive agent, and 1-20% of the binder. The binder prepared by the method of the present invention has a short production cycle and high production efficiency; the method of the present invention does not require the use of a solvent in the process of preparing the binder, thereby avoiding the problem of VOC pollution in the air; the preparation method is simple, highly practical, and easy to promote; the binder prepared by the method can improve the bonding effect of the binder and the stability of the electrode membrane, thereby increasing the capacity of the electrochemical energy storage device and improving the cycle life of the electrochemical energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of binders for electrochemical energy storage devices, and in particular to a binder for electrochemical energy storage devices, a preparation method and application thereof. Background Art

[0002] As an emerging energy storage device, supercapacitors have attracted widespread attention due to their small size, good safety, light weight, high specific energy, high specific power, and no pollution. At present, they have been used in many fields such as wind power generation, solar power generation, hybrid vehicles, UPS, robot automation, subways, and military industry. With the continuous development of supercapacitors, some technical problems have also emerged.

[0003] In the 20 years since the advent of lithium-ion batteries, lithium-ion batteries have become the most widely used commercial energy storage devices. In 1992, Sony Corporation of Japan developed a commercial lithium-ion battery, including lithium cobalt oxide as the positive electrode material and graphite as the negative electrode material. Lithium cobalt oxide positive electrode material is still widely used as the main power source for most portable electronic devices. Lithium iron phosphate is currently the safest positive electrode material and is widely used in power lithium-ion batteries. It has become the current mainstream positive electrode material. The current lithium-ion battery energy storage system of ternary positive electrode materials (NCA, NCM) and negative electrode materials such as graphite or silicon carbon has become the leader and hope in the fields of power batteries and so on. Lithium-ion batteries are simply Li + The process of ion extraction and embedding between electrode materials has no additional reaction. Therefore, lithium-ion batteries have advantages such as good safety performance and excellent cycle performance. The working principle of the battery is simple, practical and has a wider range.

[0004] The electrodes of lithium-ion batteries or supercapacitors are mainly composed of active materials, conductive agents and binders. The active material of supercapacitors is mainly activated carbon. Due to the small size of activated carbon particles, large specific surface area and low tap density, its bonding effect with the current collector is poor. The binder is used to bond the electrode active material and conductive agent particles, and at the same time bond them to the surface of the metal current collector. Therefore, the quality of the mechanical properties of the binder is closely related to the cycle life of the battery. If the mechanical properties are poor, it is easy to cause the electrode sheet to pulverize during the electrochemical cycle, causing the electrode material to fall off from the surface of the current collector and lose the electrochemical energy storage performance. At the same time, since the electrode active material is prone to volume expansion and contraction during the charging and discharging process, the electroactive material on the electrode is pulverized and falls off, eventually leading to capacity decay.

[0005] At present, the commonly used adhesives for lithium-ion batteries or supercapacitors are PTFE and PVDF. Although they have excellent electrochemical stability, they are expensive and have poor flexibility, and cannot meet the requirements of long-term battery cycles. In addition, their molecular weight decreases and their viscosity deteriorates after absorbing water, so they have relatively high requirements for environmental humidity; they are insulative to ions and electrons and swell to a certain extent in the electrolyte. At the same time, polymer adhesives based on PTFE and PVDF can only solidify electrode material particles in one or two dimensions, so during charging and discharging, there will be problems with the material falling off the current collector. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art. The present invention proposes a binder for electrochemical energy storage devices, a preparation method and its application, which utilizes the cross-linking reaction characteristics of the binder and the cross-linking agent at a certain temperature to cross-link the binder in the electrode into a network structure with good rigidity and adhesion.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: an application of a binder for an electrochemical energy storage device, wherein the binder is applied to the preparation process of an electrode sheet, wherein the electrode sheet is composed of a powder active substance, a powder conductive agent, and a binder, and comprises, by mass fraction: 70-98% of the powder active substance, 1-10% of the powder conductive agent, and 1-20% of the binder.

[0008] The binder is composed of polyacrylate with epoxy groups and a crosslinking agent, and the added amount of the crosslinking agent is 10-30% of the powder binder.

[0009] The polyacrylate with epoxy group is polymerized from the following monomers:

[0010]

[0011] The structure of the polyacrylate with epoxy group is shown below:

[0012]

[0013] Furthermore, the electrode sheet includes, by mass fraction, 88% of powdered active material, 2% of powdered conductive agent, 10% of binder, and 30% of the mass of the powdered binder as a cross-linking agent; wherein the powdered active material is activated carbon, and the powdered conductive agent is Ketjen black.

[0014] Furthermore, the method for preparing the electrode sheet comprises the following steps:

[0015] S1. After the powdered active material, the powdered conductive agent and the binder are mixed, a solvent is added to the mixture to form a slurry, wherein the viscosity of the slurry is 9500cp;

[0016] S2. Apply the slurry obtained in S1 onto the current collector and dry it to obtain an electrode sheet for an electrochemical energy storage device.

[0017] Furthermore, the initiator is a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, tert-butyl peroxide 2-ethylhexanoate, tert-amyl peroxide 2-ethylhexanoate, di-tert-butyl peroxide, initiator C, di-tert-amyl peroxide, and benzoyl peroxide.

[0018] Furthermore, the molecular weight of the polyacrylate with epoxy group is 50,000-1,000,000, and the glass transition temperature is 30-50°C.

[0019] Furthermore, the cross-linking agent is a polyamine compound or an acid anhydride compound.

[0020] Furthermore, the preparation process is carried out in an extruder, and a mixture of monomers and initiators is fed into a feed port and subjected to an extrusion polymerization reaction in the extruder. After the reaction is completed, unreacted monomers and decomposition products of the initiator are removed at a vacuum devolatilization port, and the final product is obtained by extruding, drawing, cooling, and pelletizing.

[0021] Furthermore, during the extrusion process, the feed port temperature is 30-90°C, the polymerization section temperature is 100-150°C, the devolatilization port temperature is 170-180°C, and the discharge port temperature is 100-170°C; the extrusion process is carried out in an inert environment, and the pressure in the polymerization section is 0-0.5MPa.

[0022] Compared with the prior art, the beneficial effects of the present invention include:

[0023] (1) The binder prepared by the method of the present invention has a short production cycle and high production efficiency;

[0024] (2) The method of the present invention does not require the use of solvents in the process of preparing the binder, thus avoiding the problem of VOC pollution in the air;

[0025] (3) The preparation method of the present invention is simple, practical, and easy to promote;

[0026] (4) The binder prepared by the method of the present invention can improve the bonding effect of the binder and the stability of the electrode membrane, thereby increasing the capacity of the electrochemical energy storage device and improving the cycle life of the electrochemical energy storage device. DETAILED DESCRIPTION

[0027] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes and drawings are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.

[0028] A binder for an electrochemical energy storage device, wherein the binder is applied to the preparation process of an electrode sheet; in the process of preparing the electrode sheet, the electrode sheet is composed of a powder active substance, a powder conductive agent, and a binder, and the weight fraction includes: 70-98% of the powder active substance, 1-10% of the powder conductive agent, and 1-20% of the binder;

[0029] The aforementioned binder is composed of polyacrylate with epoxy groups and a crosslinking agent, and the amount of the crosslinking agent added is 10-30% of the powder binder. The aforementioned polyacrylate with epoxy groups is polymerized by the following monomers:

[0030]

[0031] The structure of the polyacrylate with epoxy group is shown below:

[0032]

[0033] The initiator is a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, tert-butyl peroxide 2-ethylhexanoate, tert-amyl peroxide 2-ethylhexanoate, di-tert-butyl peroxide, initiator C, di-tert-amyl peroxide, and benzoyl peroxide; the molecular weight of the polyacrylate with epoxy group is 50000-1000000, and the glass transition temperature is 30-50°C; the crosslinking agent is a polyamine compound or an acid anhydride compound.

[0034] The method for preparing the electrode sheet comprises the following steps:

[0035] S1. After mixing the powdered active material, the powdered conductive agent and the binder, a solvent is added to the mixture to form a slurry, and the urea content of the slurry is 9500cp;

[0036] S2. Apply the slurry obtained in S1 onto the current collector and dry it to obtain an electrode sheet for an electrochemical energy storage device.

[0037] A method for preparing a binder for an electrochemical energy storage device. The preparation process is carried out in an extruder. A mixture of a monomer and an initiator is fed into a feed port and subjected to an extrusion polymerization reaction in the extruder. After the reaction is completed, unreacted monomers and initiator decomposition products are removed at a vacuum devolatilization port. The final product is obtained by extruding, drawing, cooling and pelletizing.

[0038] During the extrusion process, the feed port temperature is 30-90°C, the polymerization section temperature is 100-150°C, the devolatilization port temperature is 170-180°C, and the discharge port temperature is 100-170°C; the extrusion process is carried out in an inert environment, and the pressure in the polymerization section is 0-0.5MPa.

[0039] The technical effects of the present application are further described below in conjunction with embodiments.

[0040] Example 1

[0041] Preparation of polyacrylate containing epoxy groups

[0042] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 50 / 30 / 8 / 10 / 2. During mixing, control the temperature below 50°C, and cool to below 30°C after mixing;

[0043] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0044] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The feed zone temperature was adjusted to 40°C, zones 2 to 6 to 115-130°C, zones 7 and 8 to 174°C, and zones 9 and 10 to 130°C. The eighth zone was equipped with a vacuum devolatilization device to remove unreacted monomers and initiator decomposition products.

[0045] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0046] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0047] (5) 9.8 kg of activated carbon, 0.1 kg of epoxy-containing polyacrylate obtained in (1-4), 0.02 kg of cross-linking agent phthalic anhydride, and 0.1 kg of Ketchen black were dry-mixed evenly using a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0048] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.67 g / cm 3 .

[0049] Electrochemical performance of electrochemical energy storage device monomer

[0050] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 96.3% from 0.1A / g to 2A / g.

[0051] Example 2

[0052] Preparation of polyacrylate containing epoxy groups

[0053] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 45 / 30 / 13.5 / 10 / 1.5. During mixing, control the temperature below 50° C. and cool to below 30° C. after mixing;

[0054] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0055] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The temperature of the feed zone was adjusted to 43°C, zones 2 to 6 to 120-137°C, zones 7 and 8 to 175°C, and zones 9 and 10 to 130°C. The eighth zone was equipped with a vacuum devolatilization device to remove unreacted monomers and initiator decomposition products.

[0056] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0057] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0058] (5) 9.2 kg of activated carbon, 0.4 kg of epoxy-containing polyacrylate obtained in (1-4), 0.04 kg of cross-linking agent phthalic anhydride, and 0.4 kg of Ketchen black were dry-mixed by a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0059] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.62 g / cm 3 .

[0060] Electrochemical performance of electrochemical energy storage device monomer

[0061] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, and AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 97.3% from 0.1A / g to 2A / g.

[0062] Example 3

[0063] Preparation of polyacrylate containing epoxy groups

[0064] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 47 / 30 / 11.7 / 10 / 1.3. During mixing, control the temperature below 50° C. and cool to below 30° C. after mixing.

[0065] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0066] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The feed zone temperature was adjusted to 65°C, zones 2 to 6 to 130-150°C, zones 7 and 8 to 178°C, and zones 9 and 10 to 120°C. The eighth zone was equipped with a vacuum devolatilization device to remove unreacted monomers and initiator decomposition products.

[0067] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0068] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0069] (5) 8.6 kg of activated carbon, 0.8 kg of epoxy-containing polyacrylate obtained in (1-4), 0.24 kg of cross-linking agent phthalic anhydride, and 0.6 kg of Ketchen black were dry-mixed evenly using a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0070] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.59 g / cm3 .

[0071] Electrochemical performance of electrochemical energy storage device monomer

[0072] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, and AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 96.8% from 0.1A / g to 2A / g.

[0073] Example 4

[0074] Preparation of polyacrylate containing epoxy groups

[0075] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 40:30:19:10:1. During mixing, control the temperature below 50°C, and cool to below 30°C after mixing;

[0076] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0077] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The feed zone temperature was adjusted to 60°C, zones 2 to 6 to 100-110°C, zones 7 and 8 to 170°C, and zones 9 and 10 to 100°C. The eighth zone was equipped with a vacuum devolatilization device to remove unreacted monomers and initiator decomposition products.

[0078] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0079] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0080] (5) 8.8 kg of activated carbon, 1 kg of epoxy-containing polyacrylate obtained in (1-4) above, 0.3 kg of cross-linking agent phthalic anhydride, and 0.2 kg of Ketchen black were dry-mixed evenly using a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0081] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.62 g / cm 3 .

[0082] Electrochemical performance of electrochemical energy storage device monomer

[0083] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 97% from 0.1A / g to 2A / g.

[0084] Example 5

[0085] Preparation of polyacrylate containing epoxy groups

[0086] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 52 / 30 / 7 / 10 / 1. During mixing, control the temperature below 50°C, and cool to below 30°C after mixing;

[0087] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0088] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The feed zone temperature was adjusted to 60°C, zones 2 to 6 to 100-134°C, zones 7 and 8 to 170°C, and zones 9 and 10 to 100°C. The eighth zone was equipped with a vacuum devolatilization device to remove unreacted monomers and initiator decomposition products.

[0089] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0090] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0091] (5) 7.6 kg of activated carbon, 1.4 kg of epoxy-containing polyacrylate obtained in (1-4) above, 0.14 kg of cross-linking agent phthalic anhydride, and 1 kg of Ketchen black were dry-mixed evenly using a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0092] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.61 g / cm 3 .

[0093] Electrochemical performance of electrochemical energy storage device monomer

[0094] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, and AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 97.4% from 0.1A / g to 2A / g.

[0095] Example 6

[0096] Preparation of polyacrylate containing epoxy groups

[0097] (1) Mix the raw materials in a stirring mixing tank in a weight percentage ratio of methyl methacrylate / glycidyl methacrylate / isooctyl acrylate / lauryl methacrylate / azobisisobutyronitrile of 57.5 / 30 / 2 / 10 / 0.5. During mixing, control the temperature below 50° C. and cool to below 30° C. after mixing;

[0098] (2) introducing nitrogen or argon into the twin-screw extruder for purging and purification;

[0099] (3) The mixture was pumped into the feed zone of a co-rotating, tightly meshed twin-screw extruder at a rate of 10 kg / h. The extruder had a diameter of 35.6 mm and an aspect ratio of 50. The temperature of the feed zone was adjusted to 90°C, zones 2 to 6 to 125-141°C, zones 7 and 8 to 180°C, and zones 9 and 10 to 170°C. The eighth zone was equipped with a vacuum devolatilization device to remove the unreacted monomers and initiator decomposition products.

[0100] (4) After the polymerization is completed, the extrusion, drawing, cooling and pelletizing are carried out at the discharge port.

[0101] Preparation of Electrode Sheets for Electrochemical Energy Storage Devices

[0102] (5) 7 kg of activated carbon, 2 kg of epoxy-containing polyacrylate obtained in (1-4) above, 0.6 kg of cross-linking agent phthalic anhydride, and 1 kg of Ketchen black were dry-mixed evenly using a vacuum beater, and then added to 15 kg of solvent NMP for 4 h, and the slurry viscosity was adjusted to 9500 cp;

[0103] (6) The slurry obtained in step (5) is evenly coated on a 20 μm corroded aluminum foil using a transfer coater and dried at 120°C to obtain an electrode with a total thickness of 260 μm on both sides. At this baking temperature, the phthalic anhydride crosslinking agent and the epoxy-containing polyacrylate binder undergo a crosslinking reaction to form a three-dimensional network structure. The electrode compaction density is 0.65 g / cm 3 .

[0104] Electrochemical performance of electrochemical energy storage device monomer

[0105] The electrode in (6) was made into a soft-pack monomer and injected with 1 mol / L SBPBF 4 / AN system organic electrolyte, and carried out electrochemical performance tests: cyclic voltammetry test, constant current charge and discharge test, and AC impedance test. The results showed that the single-cell specific capacity was 28.55F / g, and the capacity retention rate was 96.8% from 0.1A / g to 2A / g.

[0106] The present invention uses a polymer containing an epoxy group as a binder for an electrochemical energy storage device during the electrode sheet manufacturing process, and simultaneously adds a certain amount of a curing agent as a cross-linking agent. The binder in the electrode sheet is cross-linked into a network structure with good rigidity and adhesion by utilizing the cross-linking reaction characteristics of the binder and the cross-linking agent at a certain temperature.

[0107] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of ​​the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.

Claims

1. An application of a binder for an electrochemical energy storage device, characterized in that: The binder is applied to the preparation process of the electrode sheet, which is composed of powder active material, powder conductive agent and binder, and includes, by mass fraction: 70-98% of powder active material, 1-10% of powder conductive agent, and 1-20% of binder. The binder is composed of polyacrylate with epoxy groups and a crosslinking agent, and the amount of the crosslinking agent added is 10-30% of the binder; The polyacrylate with epoxy group is polymerized from the following monomers, calculated by mass fraction: Methyl methacrylate 40-57.5%, Glycidyl methacrylate 30%, Isooctyl acrylate 2-20%, Lauryl methacrylate 10%, Initiator 0.5-2%, The structure of the polyacrylate with epoxy group is shown below: ; The initiator is a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, tert-butyl peroxide 2-ethylhexanoate, tert-amyl peroxide 2-ethylhexanoate, di-tert-butyl peroxide, initiator C, di-tert-amyl peroxide, and benzoyl peroxide; the molecular weight of the polyacrylate with epoxy group is 50,000-1,000,000, and the glass transition temperature is 30-50° C.; and the crosslinking agent is a polyamine compound or anhydride compound.

2. The use of the binder for electrochemical energy storage devices according to claim 1, characterized in that: The electrode sheet includes, by mass fraction, 88% of powdered active material, 2% of powdered conductive agent, and 10% of binder, and the binder also includes a cross-linking agent that is 30% of the mass of the powdered binder; The powder active material is activated carbon, and the powder conductive agent is Ketjen black.

3. The use of the binder for electrochemical energy storage devices according to claim 2, characterized in that: The method for preparing the electrode sheet comprises the following steps: S1. After the powdered active material, the powdered conductive agent and the binder are mixed, a solvent is added to the mixture to form a slurry, wherein the viscosity of the slurry is 9500cp; S2. Apply the slurry obtained in S1 onto the current collector and dry it to obtain an electrode sheet for an electrochemical energy storage device.

Citation Information

Patent Citations

  • Concurrently curable hybrid adhesive composition

    CN101297011A

  • Bond made from halogen-free sheet soft magnetic material, preparation method thereof and halogen-free soft magnetic sheet

    CN103409086A

  • Negative pole binder, preparation method therefor and preparation method for negative pole piece

    CN108203482A